Cuidados al adulto mayor residente en el centro geriatrico "Hogar de Nazaret" de la parroquia Paccha durante los meses de octubre a diciembre del año 2013. - Lindao Arreaga, Jomayra Aracely (2015)
This research titled CARE TO ELDERLY LIVING IN THE GERIATRICO "HOME OF NAZARETH" Paccha PARISH CENTER During October to December 2013, it was conducted through a descriptive cross-sectional study, using the survey as a technique, we worked with the variables individual characteristics, types of diseases and types of care offered by the staff. The universe was composed of 47 elderly and the sample for 100% of the total population.